2016
DOI: 10.2166/wst.2016.405
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of sewage and industrial effluent using bacterially assisted floating treatment wetlands vegetated with Typha domingensis

Abstract: This investigation reports the quantitative assessment of endophyte-assisted floating treatment wetlands (FTWs) for the remediation of sewage and industrial wastewater. Typha domingensis was used to vegetate FTWs that were subsequently inoculated with a consortium of pollutant-degrading and plant growth-promoting endophytic bacteria. T. domingensis, being an aquatic species, holds excellent potential to remediate polluted water. Nonetheless, investigation conducted on Madhuana drain carrying industrial and sew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The hanging roots of plants below mat provide a large area for biofilms development and wastewater treatment . This is the reason that FTWs even have been proved effective for treatment of polluted surface water, sewage, industrial, and agricultural wastewater . Retention ponds are efficient to remove coarse and particulate forms of contaminants but not capable of removing dissolved contaminants effectively .…”
Section: Benefits Of Ftwsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hanging roots of plants below mat provide a large area for biofilms development and wastewater treatment . This is the reason that FTWs even have been proved effective for treatment of polluted surface water, sewage, industrial, and agricultural wastewater . Retention ponds are efficient to remove coarse and particulate forms of contaminants but not capable of removing dissolved contaminants effectively .…”
Section: Benefits Of Ftwsmentioning
confidence: 99%
“…[17] This is the reason that FTWs even have been proved effective for treatment of polluted surface water, sewage, industrial, and agricultural wastewater. [10,14,34,65,95,170] Retention ponds are efficient to remove coarse and particulate forms of contaminants but not capable of removing dissolved contaminants effectively. [171] Although constructed wetlands can efficiently remove soluble pollutants and associated fine particles, these wetlands need large area and are unable to tolerate extended duration of high water levels.…”
Section: Carex Virgatamentioning
confidence: 99%
See 1 more Smart Citation
“…Higher numbers of bacterial populations were counted in the T3 treatment; it was due to the efficient plant bacterial partnership. As reported by the previous study that plant roots provide residency and nutrients for proliferation of bacterial community present in outer and inner part of the tissues of the plant [52]. It has also been reported that rhizo bacteria that are involved in plant growth are probably to be present in inner tissue of plant (endophyte bacteria) at particular phase of their lifecycle so microbes can effectively penetrate in exposed plant parts especially in root and process of colonization of bacteria occurs by a dynamic mechanism for pollutant removal [23,53].…”
Section: Persistence Of Microbial Populationmentioning
confidence: 74%
“…This technique provides a means of in situ treatment of contaminated land with high efficiency using natural biological activity. In plant-microbe synergism, plants offer nutrients and habitat to their associated bacteria and in return, microbes enhance plant growth and detoxify environmental pollutants (Chaudhry et al, 2005;Compant et al, 2010;Glick, 2010;Sessitsch et al, 2013;Afzal et al, 2014a;Ijaz et al, 2015bIjaz et al, , 2016Ahmed et al, 2017).). In this review, the contamination of environment with crude oil, remediation of soil contaminated with crude oil, plantbacterial synergism in phytoremediation, and role of rhizoand endophytic bacteria for the maximum remediation of the soil, are discussed.…”
mentioning
confidence: 99%